Differential regulation of the c-myc oncogene promoter by the NF-kappa B rel family of transcription factors. - La Rosa, F A (1994)
The murine c-myc gene contains two elements responsive to the rel-oncogene-related family of NF-kappa B factors. Previously we have shown that factor binding to these two NF-kappa B elements mediates induction of transcription of the c-myc promoter upon interleukin-1 treatment of human dermal fibroblasts and human T-cell leukemia virus type I tax gene expression in T cells (D. J. Kessler, M. P. Duyao, D. B. Spicer, and G. E. Sonenshein, J. Exp. Med. 176:787-792, 1992; M. P. Duyao, D. J. Kessler, D. B. Spicer, C. Bartholomew, J. L. Cleveland, M. Siekevitz, and G. E. Sonenshein, J. Biol. Chem. 267:16288-16291, 1992). To begin to delineate the specific roles of the individual members of the NF-kappa B family, here we have tested their effects on activation of a c-myc promoter/exon 1-CAT construct in NIH 3T3 cells. Classical NF-kappa B (p65/p50) was a potent transcriptional activator of the c-myc promoter. Cotransfection with either p65 alone or p65 in combination with p50 mediated significant induction. In contrast, expression of either v-rel or chicken c-rel failed to transactivate, while murine c-rel induced c-myc promoter activity only slightly. Furthermore, induction by classical NF-kappa B was inhibited by coexpression of either v-rel or chicken c-rel. Thus, individual members of the rel family have differential effects of the c-myc promoter, which can modulate overall transcriptional activity and allow for precise regulation of this oncogene under diverse physiologic conditions.